Periocular arteriovenous malformation in child treated with surgical excision – a case report - Niwald, Anna; Grałek, Mirosława; Kobos, Józef; Kobielski, Artur (Klinika Oczna / Acta Ophthalmologica Polonica, 2018)
Arteriovenous malformations are rare congenital anomalies caused by disturbances in vascular morphogenesis. These malformations do not resolve spontaneously. If located in periocular region, they may result not only in aesthetics defects, but also impair visual function to a varying degree. We describe the case of a 13-year old girl with a right-sided periocular arteriovenous malformation, involving the orbit and the upper eyelid. The in-depth diagnostic management included magnetic resonance imaging. The malformation was treated with surgical excision and the postoperative history was uneventful. Good aesthetic effect and visual function improvement were achieved.